Sanders hotel and store showing woman standing next to laundry line, Skagway, probably between 1897 and 1899 - Warner, Arthur Churchill, 1864-1943 (1897)
After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897. Warner 103 Filed in Alaska series.